Studi Literatur: Profil Lipid pada Subjek Dislipidemia dengan Pemberian Ekstrak Allium sativum L - Parmasari, Wahyuni Dyah; I Gede Paskha Yustiana (Calvaria Medical Journal, 2026)
Background: Dyslipidemia is a lipid metabolism disorder characterized by increased levels of total cholesterol, low-density lipoprotein (LDL), triglyceride levels, and low levels of high-density lipoprotein (HDL) in the blood. Garlic (Allium sativum L.) is a plant used as an herbal medicine and has been traditionally used to treat various health conditions. Compounds in garlic have lipid-lowering effects and antiplatelet activity. Objective: This study was to determine the effect of garlic extract (Allium sativum L.) on dyslipidemia. Method: Literature study conducted by collecting data through electronic-based literature searches using the internet by Google Scholar, ResearchGate, PubMed, dan Proquest. Results: This article review demonstrates that garlic extract (Allium sativum L.) affects dyslipidemia. Pure, unprocessed garlic extract can reduce total cholesterol levels and other markers, such as triglycerides and LDL (low-density lipoprotein) levels. Conclusion: Garlic (Allium sativum L.) has a role in dyslipidemia; garlic extract can reduce total cholesterol levels